Penerapan Produksi Ramah Lingkungan Pada Proses Produksi UKM Batik Tulis - Ong Wahyu Riyanto; Subaderi Subaderi; Ahmad Sholikhul Nafi (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Many Batik SMEs that have developed in the city of Sidoarjo Regency, East Java, are indicated as a cause of environmental pollution caused by the use of chemicals in the batik production process. The majority of the batik production process uses chemical dyes which are categorized as not sustainable but affordable (economically feasible). To increase the eco-efficiency level can be done by increasing the selling price, reducing production costs or creating clean production that can be done using alternative dyes (natural dyes) and applying the end of life strategy through: 1) Application of appropriate technology for dyeing batik cloth in the coloring process. 2) Conversion of fuel using a 3 kg LPG tube. 3) Making simple kowen. 4) Application of wastewater treatment plants (IPAL) with electrocoagulant technology. The most suitable technology alternative to be applied to UKM of Jetis Batik in Sidoarjo Regency, Sidoarjo is the application of appropriate technology to dye batik cloth in the coloring process. With the application of appropriate technology, dyeing batik cloth in the coloring process will be able to increase eco-efficiency in the production process of UKM Batik Tulis, Jetis Sidoarjo Village.